(untitled) (Web of Teachers: Inderscience Research, 2025)
The method of forming is a sense of responsibility among preschoolers include suggestions for improvement through the use of integrative capabilities based on observation of the difficulties of dialogical relations in a differentiated learning environment, educational and socio-pedagogical processes. Important signs of socio-pedagogical cooperation are mutual understanding, mutual relationships, mutual actions, cooperation, interaction, compatibility. The article was highlighted the cooperation of the pedagogical process, the types of interaction, as well as the importance of teacher-parent cooperation in developing preschoolers’ sense of responsibility.